2019
DOI: 10.3390/su11061510
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability of Cruise Tourism Onshore: The Impact of Crowding on Visitors’ Satisfaction

Abstract: The sustainability of cruise tourism has been questioned in relation to its negative effects on ports of call, among which crowding has recently become more pronounced. However, an understanding of how crowdedness influences cruise tourists' experience onshore is lacking. The study analyzed online reviews on onshore experiences in the main European ports of call through Leximancer, an automated text analytics software. The results revealed that the perceived destination crowding was not always negatively evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 63 publications
0
31
0
5
Order By: Relevance
“…The phenomenon of overtourism has been studied in many European cities such as Madrid and Palma de Mallorca [19], and its effects have been described in relation to Krakow [8,20] and Ljubljana [7]. Excessive numbers of tourists are observed in many port cities thanks to cruise tourism [21]. However, research in 13 European cities such as Amsterdam, Berlin, Copenhagen, Lisbon, and Tallinn indicates abuse of the term 'overtourism' (overtourism overused) and seven myths attributed to this phenomenon [22].…”
Section: Overtourism As a Factor In Unsustainable Developmentmentioning
confidence: 99%
“…The phenomenon of overtourism has been studied in many European cities such as Madrid and Palma de Mallorca [19], and its effects have been described in relation to Krakow [8,20] and Ljubljana [7]. Excessive numbers of tourists are observed in many port cities thanks to cruise tourism [21]. However, research in 13 European cities such as Amsterdam, Berlin, Copenhagen, Lisbon, and Tallinn indicates abuse of the term 'overtourism' (overtourism overused) and seven myths attributed to this phenomenon [22].…”
Section: Overtourism As a Factor In Unsustainable Developmentmentioning
confidence: 99%
“…Hosany and Witham (2010) analyzed the tourist cruise experience dimension and recommendation intention and satisfaction in the entertainment, aesthetic, and education, from four dimensions of experience, had the strongest influence on satisfaction and recommendation intention, while aesthetic experience, entertainment, education, and escape had different degrees of influence [44]. Silvia et al (2019) not only regarded familiarity and visit characteristics as determinants of tourists' experience at a cruise destination, but also cared about the impact of crowding on visitors' satisfaction for the sustainability of cruise tourism onshore [45,46].…”
Section: Cruise Company Value Chainmentioning
confidence: 99%
“…Recently, the World Tourism Organization reported that the sustainable development of cruising activities is needed to balance between socio-cultural, environmental, and economic areas [27]. Sustainable cruising development fulfils the needs of current tourists and grasps the future opportunities [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainable cruising development fulfils the needs of current tourists and grasps the future opportunities [28]. To this end, the negative impacts of cruising activities on society, the environment, and economy could be decreased accordingly [27]. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%